2020
DOI: 10.1039/d0tb00223b
|View full text |Cite
|
Sign up to set email alerts
|

Joint construction of micro-vibration stimulation and BCP scaffolds for enhanced bioactivity and self-adaptability tissue engineered bone grafts

Abstract: The bone defects caused by trauma and disease have become a major difficulty in the treatment of clinical bone defects, and bone tissue engineering has become a promising treatment strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…The threshold of defect was 459mg/cm3 (the amount containing hydroxyapatite per cubic centimeter). 20 random sectional images of each sample at each time point were evaluated visually, the threshold that could best describe the morphology of mineralized tissue was selected, and scaffolds and soft tissues [ 25 ] were excluded to determine these indicators. In VOI, the following parameters were measured: bone tissue volume (BV), bone tissue volume/total tissue volume (BV/TV), axial BV distribution, radial bone volume distribution, bone mineral density (BMD) and statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The threshold of defect was 459mg/cm3 (the amount containing hydroxyapatite per cubic centimeter). 20 random sectional images of each sample at each time point were evaluated visually, the threshold that could best describe the morphology of mineralized tissue was selected, and scaffolds and soft tissues [ 25 ] were excluded to determine these indicators. In VOI, the following parameters were measured: bone tissue volume (BV), bone tissue volume/total tissue volume (BV/TV), axial BV distribution, radial bone volume distribution, bone mineral density (BMD) and statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…For example, mechanical vibration (0.3 g, 30 Hz) for 8 weeks enhances porous titanium implant integration with bone tissue in diabetic rabbits [29]. Periodic vibration (0.3 g, 40 Hz) upregulates the osteoinduction capacity of biphasic calcium phosphate (BCP) scaffolds [30]. Low pulse vibration (0.25 N, 30 Hz) for 48 h reduces RANKL production of osteoblasts and increases osteoclastic marker cathepsin K levels in bone marrow cells [22].…”
Section: Discussionmentioning
confidence: 99%
“…Ye X et al [50] wrapped autologous ASCs with calcium alginate gel and implanted them into the distal femur of OVX rabbits and found that the femoral bone mineral density of OVX rabbits in the composite ASCs group increased signi cantly and promoted the formation of new bone. BCP is a new type of biological scaffold material that provides su cient space for cell attachment, growth, and proliferation [51,52]. Rath SN et al found that BMSCs can proliferate on BCP and promote bone formation following osteogenic induction [53].…”
Section: Discussionmentioning
confidence: 99%